2007
DOI: 10.1071/sr07069
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phosphorus fractions at various soil depths following long-term P fertiliser application on a Black Vertosol from south-eastern Queensland

Abstract: Long-term removal of grain P and soil test data suggested that the Colwell phosphorus (P) extraction from the surface 0.10 m of a Black Vertosol from south-eastern Queensland was a poor indicator of run-down of soil P pools. We proposed that plants were also accessing P from layers below 0.10 m or from surface soil P pools not extracted by the Colwell extraction. Both topsoil and subsoil samples in 1994 and 2003 were collected from nil and 20 kg P/ha per crop treatments in a long-term N × P field experiment es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 49 publications
4
43
5
Order By: Relevance
“…The main reason is the very high phosphate fixation capacity of soil materials, and thus there are few examples in which subsurface soils show a response to chronic P additions (cf. Wang et al 2007;Rivaie et al 2008). However, our data agree with Wagar et al (1986) that P o is more mobile than P i , and thus P o in the labile fraction with added P moves downward more readily than P i .…”
Section: Impact Of Chronic Nutrient Additioncontrasting
confidence: 42%
“…The main reason is the very high phosphate fixation capacity of soil materials, and thus there are few examples in which subsurface soils show a response to chronic P additions (cf. Wang et al 2007;Rivaie et al 2008). However, our data agree with Wagar et al (1986) that P o is more mobile than P i , and thus P o in the labile fraction with added P moves downward more readily than P i .…”
Section: Impact Of Chronic Nutrient Additioncontrasting
confidence: 42%
“…Similarly, in an Oxisol, Buhler et al (2002) reported that the NaOH-Pi was the main sink for the applied P. The dynamics of the NaOH-Pi can be explained by the adsorption of Pi through ligand exchange with hydroxyl groups located on the surface of Fe and Al oxides/hydroxides, and the desorption of Pi from the surface of oxides/hydroxides in the presence of 0.5 M NaOH (Tan 1998;Vu 2004). The transformation of the added P into the acid-extractable P fraction in Vertosols is in agreement with previous studies showing that acid-extractable P was the highest P pool in the same soil type (Wang et al 2007;Vu et al 2009). Alternatively, the predominance of Pi extracted by the acids compared to the alkali may reflect the strong association of P with Ca.…”
Section: The Fate Of Applied P In Different Soil Typessupporting
confidence: 90%
“…For the clay soil, increased root proliferation in the subsoil due to surface drought was possibly counter-balanced by net root loss in the dry topsoil, resulting in a similar total root dry weight to that with topsoil watering. The potential benefit of subsoil P sources and application has been demonstrated in many studies (Haak 1977;Kuhlmann and Baumgartel 1991;Norrish et al 2003;Singh et al 2005;Wang et al 2007). Frequent surface drought decreases both root growth and function in the topsoil (Puroit and Mukherjee, 1974) but increases the significance of subsoil P nutrition.…”
Section: Hydraulic Liftmentioning
confidence: 94%